2018
DOI: 10.1021/acsami.8b04470
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antimicrobial Activity and Structural Transitions of a Nanofibrillated Cellulose–Nisin Biocomposite Suspension

Abstract: Resistance to antibiotics has posed a high demand for novel strategies to fight bacterial infections. Antimicrobial peptides (AMPs) are a promising alternative to conventional antibiotics. However, their poor solubility in water and sensitivity to degradation has limited their application. Here, we report the design of a smart, pH-responsive antimicrobial nanobiocomposite material based on the AMP nisin and 2,2,6,6-tetramethyl-1-piperidinyloxyl-oxidized nanofibrillated cellulose (TONFC). Morphological transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 66 publications
0
36
1
Order By: Relevance
“…This so‐called substrate effect can additionally change the antibacterial efficiency (MIC) of AMPs in response to the underlying material. [ 35 ] Despite considerable differences in the macroscopic and microscopic morphology between BC films and CPU membranes, our data do not give evidence for such a material‐induced effect. This can be attributed to the architectural structure in the micrometer to sub‐micrometer range that is by magnitudes larger than the dimensions of nanofibrillated cellulose (NFC, 10–20 nm) where such an effect was observed.…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…This so‐called substrate effect can additionally change the antibacterial efficiency (MIC) of AMPs in response to the underlying material. [ 35 ] Despite considerable differences in the macroscopic and microscopic morphology between BC films and CPU membranes, our data do not give evidence for such a material‐induced effect. This can be attributed to the architectural structure in the micrometer to sub‐micrometer range that is by magnitudes larger than the dimensions of nanofibrillated cellulose (NFC, 10–20 nm) where such an effect was observed.…”
Section: Resultscontrasting
confidence: 65%
“…Previous work in our group reported on enhanced antimicrobial activity of a nanocellulose‐nisin biocomposite, exposed to bacteria in suspension compared to nisin alone. [ 35 ] The study indicated no direct correlation of the activity of material‐tethered AMP nisin with the activity, or MIC, of nisin in suspension. It is suggested that the increased activity can arise from controlled orientation and thus increased availability of peptides on the nanocarriers.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Overall the nisin active PLA-CNC film contained all three essential packaging properties: antimicrobial activity, strength and biodegradability. Weishaupt et al [75] reported the self-assembly of nanofibrilled cellulose-nisin biocomposite. TEMPO-oxidized nano-fibrillated cellulose containing carboxylic groups provided a negative surface for nisin to be adsorbed onto the surface [75].…”
Section: Cncs As Antimicrobial Agent Carriersmentioning
confidence: 99%
“…Weishaupt et al [75] reported the self-assembly of nanofibrilled cellulose-nisin biocomposite. TEMPO-oxidized nano-fibrillated cellulose containing carboxylic groups provided a negative surface for nisin to be adsorbed onto the surface [75]. The binding of nisin to nanocellulose was greatly affected by electrostatic interactions.…”
Section: Cncs As Antimicrobial Agent Carriersmentioning
confidence: 99%